(untitled) (Journal of European Studies (JES), 2019)
This article describes the establishment and evolution of the British National Health Service (NHS). It delineates its structure and operating mechanism along with the pressures it has had to face in the last seven decades since its conception. It then compares the details with the healthcare sector in Pakistan. It holds that public spending on health and medicine in Pakistan does not encompass the rapidly changing demographics and urbanization. Additionally, the NHS could provide a way forward for any meaningful and substantive state intervention in this regard. The article concludes with some policy suggestions that in the opinion of the authors if implemented may offset the growing challenges in the public health sector.